Knowledge of obstetric danger signs among Saudi Arabian women - Amani Abu-Shaheen; Humariya Heena; Abdullah Nofal; Muhammad Riaz; Isamme AlFayyad (BMC, 2020)
Abstract Background In the Middle East, tremendous efforts have been made to promote both maternal and child health. However, there is little information in the literature about maternal knowledge of obstetric danger signs. Thus, this study aims to investigate Saudi Arabian women's knowledge of obstetric danger signs and their determinant factors. Methods A community-based, cross-sectional survey was conducted in primary health care centers (PHCCs) in Riyadh City. A proportionate random sample of women who have delivered during the past 2 years was selected from the PHCCs. Data were then collected through structured interviews; the questionnaire was developed based on the literature review. Results A random sample of 1397 women were included in the final analysis of this study. During pregnancy, 21.1% of the participants reported that they knew about swollen hands or faces. During labor, 23.1% of the participants reported that they knew about prolonged labor (> 12 h). At postpartum, 26.3% of the participants reported that they knew about foul-smelling vaginal discharge. In this study, women in the northern region of Riyadh who visited government hospitals had significantly higher odds of knowing at least one obstetric danger sign. A statistically significant difference was found between the participants' knowledge of at least one obstetric danger sign and her 11-15 times of antenatal care visit. Conclusions A dedicated health education guide, and a kingdom-wide maternal and child health preventive care promotion program could improve the health and wellbeing of expectant mothers. In these programs, it is essential to focus on birth preparedness, with danger signs recognition, and the integrate health-related data for the whole kingdom.